A novel approach for comparison of reception performance in a technique test and small-sided games - Sorensen, A.; Sorensen, V.; Dalen, T. (Sports, 2021)
The purpose of this study was to evaluate the correlation between soccer players` performance of receptions of passes in tests of both isolated technical skills and more match-realistic situations in small-sided games (SSGs). In addition, this study investigated whether the involvement in SSGs (number of receptions) correlated with the quality of receptions in the respective SSGs. The participants were 13 male outfield youth soccer players from teams in the first division of the regional U18 league. The quality of receptions was scored by educated coaches according to set criteria of performance. Statistical analyses of correlations were determined using Spearman`s rank-order correlation coefficient (rs). The main results were (1) a significant correlation in the quality of ball reception between 4vs1 SSGs and 5vs5 SSGs (rs = -0.61, p < 0.01) and (2) a trend towards moderate correlation between the quality of ball reception using a ball projection machine and 5vs5 SSGs (rs = -0.48, p = 0.10). (3) A significant correlation was found between the number of receptions in 5vs5 SSGs and the quality score of receptions in 5vs5 SSGs (rs = -0.70, p < 0.01). The trend towards moderate correlations between 5vs5 SSGs and the isolated technical reception test could imply the importance of training in the technical aspects of ball reception. Moreover, it seems as though the players with the best reception performance are the players who are most involved in SSGs, that is, having the most receptions.